Emission of nanoparticles at the crack front during cleavage of alkali-halide single crystals - Massalimov, I.A.; Madyukov, I.A.; Shevchenko, V.S.; Urakaev, F.Kh. (Functional Materials, 2005)
Equations of statistical physics are applied to numerical aspects of energy balance at the crack front with reference to the cleavage of alkali halide single crystals. The possibility of nanoparticles emission during the dynamic failure is ascertained theoretically. Рiвняння статистичної фiзики застосовано до числових аспектiв енергетичного балансу при фронтi трiщини для випадку розколювання лужногалоїдних монокристалiв. Теоретично оцiнено ймовiрнiсть утворення наночастинок у процесi динамiчного руйнування. Уравнения статистической физики применены к численным аспектам энергетического баланса у фронта трещины для случая раскалывания щелочно-галоидных монокристаллов. Теоретически оценена вероятность образования наночастиц в процессе динамического разрушения.